1 ⋅ 2 ⋅ 3 ⋅ 4 ⋅ 5 1 + 3 ⋅ 4 ⋅ 5 ⋅ 6 ⋅ 7 1 + 5 ⋅ 6 ⋅ 7 ⋅ 8 ⋅ 9 1 + ⋯ = ?
Give your answer to 3 significant figures.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
An interesting way to solve series like this would be to set up the sum as n = 1 ∑ ∞ ∫ 0 1 ∫ 0 a ∫ 0 b . . . y 2 n − 2 d y d d d c d b d a = ∫ 0 1 ∫ 0 a ∫ 0 b . . . n = 1 ∑ ∞ y 2 n − 2 d y d d d c d b d a . The sum is just a geometric progression.
Much more applicable for smaller cases.
This is a good start. However, your explanation has a slight error.
Keep writing more solutions and you will get the hang of this!
S = k = 0 ∑ ∞ ( 2 k + 1 ) ( 2 k + 2 ) ( 2 k + 3 ) ( 2 k + 4 ) ( 2 k + 5 ) 1 S = 2 4 1 k = 0 ∑ ∞ 2 k + 1 1 − 2 k + 2 4 + 2 k + 3 6 − 2 k + 4 4 + 2 k + 5 1 S = 2 4 1 k = 0 ∑ ∞ ( ∫ 0 1 ( x 2 k − 4 x 2 k + 1 + 6 x 2 k + 2 − 4 x 2 k + 3 + x 2 k + 4 ) d x ) S = 2 4 1 k = 0 ∑ ∞ ( ∫ 0 1 x 2 k ⋅ ( 1 − 4 x + 6 x 2 − 4 x 3 + x 4 ) d x ) S = 2 4 1 k = 0 ∑ ∞ ( ∫ 0 1 x 2 k ⋅ ( 1 − x ) 4 d x ) S = 2 4 1 ∫ 0 1 ( ( 1 − x ) 4 ⋅ k = 0 ∑ ∞ x 2 k ) d x S = 2 4 1 ∫ 0 1 1 − x 2 ( 1 − x ) 4 d x = 2 4 1 ∫ 0 1 1 + x ( 1 − x ) 3 d x S = 2 4 1 ∫ 0 1 ( − x 2 + 4 x − 7 + x + 1 8 ) d x S = 2 4 1 ( 3 − x 3 + 2 x 2 − 7 x + 8 ln ( x + 1 ) ∣ ∣ ∣ ∣ 0 1 ) S = 2 4 1 ( 8 ln ( 2 ) − 3 1 6 ) = 3 ln ( 2 ) − 9 2 ≈ 0 . 0 0 8 8 2 6 Using partial fractions manipulate the fractions take x 2 k as common factor interchange integral with sum k = 0 ∑ ∞ x 2 k is geometric series since ∣ x ∣ < 1 dividing the polynomials
Problem Loading...
Note Loading...
Set Loading...
Using partial fractions, for the sum S = n = 1 ∑ ∞ ( 2 n − 1 ) ( 2 n ) ( 2 n + 1 ) ( 2 n + 2 ) ( 2 n + 3 ) 1 =
2 4 1 n = 1 ∑ ∞ ( n − 2 + n + 1 − 2 + 2 n − 1 1 + 2 n + 1 6 + 2 n + 3 1 ) , disregard the 2 4 1 until the end.
n = 1 ∑ ∞ n − 2 + n + 1 − 2 = − 4 ( 1 + 2 1 + 3 1 + . . . ) + 2
n = 1 ∑ ∞ 2 n − 1 1 + 2 n + 1 6 + 2 n + 3 1 = 1 + 3 1 + 3 6 + 8 ( 5 1 + 7 1 + . . . )
3 1 6 + 8 ( 5 1 + 7 1 + . . . ) − 4 ( 1 + 2 1 + 3 1 + . . . ) =
3 1 6 − 8 ( 1 + 3 1 ) + 8 ( 1 + 3 1 + 5 1 + . . . ) − 8 [ 2 1 ( 1 + 2 1 + 3 1 + . . . ) ] =
3 − 1 6 + 8 ( 1 − 2 1 + 3 1 − . . . ) = 3 − 1 6 + 8 ln 2
Bring back the 2 4 1 , S = 3 ln 2 − 9 2 ≈ . 0 0 8 8 2 6 8 3 8